PENGARUH PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA MELALUI LESSON STUDY SISWA KELAS III - ., I Putu Dodik Anggariana; ., Drs. I Ketut Dibia,S.Pd, M.Pd; ., Prof. Dr. I Ketut Dharsana,M.Pd (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar Matematika antara siswa yang mengikuti model pembelajaran Problem Based Learning melalui Lesson Study dengan siswa yang tidak mengikuti pembelajaran Problem Based Learning melalui Lesson Study pada siswa kelas III SDN Paket Agung. Populasi penelitian adalah kelas III di SDN Paket Agung Kecamatan Buleleng tahun pelajaran 2016/2017 yang berjumlah 80 siswa. Sampel penelitian yaitu kelas III SDN 1 Paket Agung yang berjumlah 39 siswa dan kelas III SDN 2 Paket Agung yang berjumlah 41 siswa. Data skor hasil belajar Matematika dikumpulkan dengan instrumen tes pilihan ganda. Data yang dikumpulkan dianalisis menggunakan analisis statistik deskriptif dan statistik inferensial (uji-t). Hasil penelitian menunjukkan bahwa rata-rata skor hasil belajar Matematika kelompok eksperimen adalah 15,46 lebih besar dari rata-rata skor hasil belajar Matematika kelompok kontrol adalah sebesar 8,78. Ketiga hipotesis penelitian diuji dengan taraf signifikansi 5%. Setelah dilakukan perlakuan pada kelas eksperimen didapatkan Fhitung dari uji-t yaitu sebesar 14,494. Hal ini membuktikan bahwa, terdapat perbedaan yang signifikan hasil belajar Matematika antara siswa yang mengikuti model pembelajaran Problem Based Learning melalui Lesson Study dengan siswa yang tidak mengikuti pembelajaran Problem Based Learning melalui Lesson Study pada siswa kelas III SDN Paket Agung. Kata Kunci : Based Learning, Lesson Study, uji-t This research aimed to know the differences in the mathematics outcomes between groups of students that learned with Problem Based Learning by Lesson Study model and groups of students that learned without Problem Based Learning by Lesson Study in the third grade students in elementary school cluster eighth district of Buleleng. The research population is a third class in eighth cluster district of Buleleng in the academic year 2016/2017, amounting to 80 students. The research sample is fourth class in elementary school 1 Paket Agung amounting to 39 students and fourth class in elementary school 2 Paket Agung, amounting to 41 students. The mathematics outcomes score data collected by multiple choice-test instrument. Data collected were analyzed using descriptive statistical analysis and inferential statistics (t-test). The results showed that average scores of mathematics outcomes the experimental group was 15,46 higher than the average score of mathematics outcomes the control group amounted to 8,78. These three research hypotheses were tested with a significance level of 5%. After gived treatment in experiment class be obtained of Fcount = 14,494.. This proves that, existed differences mathematics outcomes between groups of students that learned with Problem Based Learning by Lesson Study model and groups of students that learned without Problem Based Learning by Lesson Study in the third grade students in elementary school cluster eighth district of Buleleng. keyword : Based Learning, Lesson Study, t-test